Knowledge, attitudes, and practices toward over-the-counter antipyretics among fever patients: a cross-sectional study in the context of a policy change KAP of OTC antipyretics - Zhang, Yan; Liang, Shuchang; Zhu, Tao (Frontiers in Public Health, 2023)
Background: On January 8, 2023, a change in the control policy for COVID-19 was implemented in China, whereby patient self-management of fever typically entails the utilization of over-the-counter fever-reducing medications. Objective: This study aimed to investigate the knowledge, attitudes, and practices (KAP) towards over-the-counter (OTC) antipyretics among fever patients. Methods: This cross-sectional study was conducted between October 2022 and February 2023 at author’s hospital in Wuhan, China, among fever patients on OTC antipyretics, using a self-administered questionnaire. Results: A total of 481 valid questionnaires were collected, with the age of 36.05 ± 12.10 years, including 240 (49.90%) males, and 209 (43.45%) collected before policy change. The knowledge, attitudes, precautions for medication administration and decision-making practices scores were 6.86 ± 3.30 (possible range: 0-12), 16.67 ± 2.46 (possible range: 7-35), 29.98 ± 5.41 (possible range: 7-35) and 27.87 ± 1.28 (possible range: 8-40), respectively. The multivariable logistic regression analysis showed that knowledge (OR=0.83, 95%CI: 0.81-0.92, P < 0.001) was independently associated with positive attitude. Knowledge (OR=1.41, 95%CI: 1.28-1.56, P < 0.001), attitude (OR=0.87, 95%CI: 0.79-0.95, P = 0.004), suburban (OR=0.45, 95%CI: 0.23-0.88, P = 0.019) were independently associated with proactive precautions for medication administration practices. Knowledge (OR=1.14, 95%CI: 1.07-1.22, P < 0.001), attitude (OR=0.90, 95%CI: 0.82-0.98, P = 0.018), responding after policy change, 2023 (OR=1.70, 95%CI: 1.10-2.63, P = 0.016) were independently associated with proactive decision making practices. Conclusion: Fever patients had moderate knowledge, negative attitude, proactive precautions for medication administration practices, moderate decision-making practices. After the policy change, there was a significant increase in knowledge regarding medication administration precautions and decision-making.